Under pressure—exploring partner changes, physiological responses and telomere dynamics in northern gannets across varying breeding conditions - Pelletier,David; Blier,Pierre U.; Vézina,François; Dufresne,France; Paquin,Frédérique; Christen,Felix; Guillemette,Magella (PeerJ, 2023)
Background Life history theory predicts trade-offs between reproduction and survival in species like the northern gannet (Morus bassanus). During breeding, demanding foraging conditions lead them to expand their foraging range and diversify their diet, increasing the risk of reproductive failure. Changing partners may enhance breeding success but lead to more physiological costs. Methods To investigate the physiological costs of reproduction upon partner changes, we measured and compared 21 biomarkers related to telomere dynamics, oxidative stress, inflammation, hematology, nutritional status, and muscle damage. We used a longitudinal approach with gannets (n = 38) over three contrasting years (2017, 2018 and 2019). Results Our results suggest that annual breeding conditions exert a greater influence on physiological changes than partnership status. Individuals that changed partner experienced greater short-term stress than retained partners. This transient increase in stress was marked by short-term increases in oxidative lipid damage, lower antioxidant capacity, signs of inflammation, and greater weight loss than individuals that retained partners. During favorable conditions, individuals that changed mates had stabilized telomere length, decreased antioxidant capacity, glucose concentration, and muscle damage, along with increased oxygen transport capacity. Conversely, unfavorable breeding conditions led to increased telomere attrition, stabilized antioxidant capacity, decreased inflammation susceptibility, diminished oxygen transport capacity, and increased muscle damage. In the cases where partners were retained, distinct physiological changes were observed depending on the year’s conditions, yet the telomere dynamics remained consistent across both partnership status categories. During the favorable year, there was an increase in unsaturated fatty acids and oxygen transport capacity in the blood, coupled with a reduction in inflammation potential and protein catabolism. In contrast, during the unfavorable year in the retained mates, we observed an increase in oxidative DNA damage, antioxidant capacity, weight loss, but a decrease in inflammation susceptibility as observed in changed mates. Discussion Our study shows that behavioral flexibility such as mate switching can help seabirds cope with the challenges of food scarcity during reproduction, but these coping strategies may have a negative impact on physiological status at the individual level. In addition, the marked reduction in telomere length observed during harsh conditions, coupled with the stabilization of telomere length in favorable conditions, highlights the long-term physiological impact of annual breeding conditions on seabirds. These findings underscore the effect on their potential survival and fitness, emphasizing that the influence of annual breeding conditions is greater than that of partnership status.
Keywords: Inflammation; Individual quality; Life history theory; Nutritional status; Oxidative stress; Physiological costs of reproduction; Telomere attrition; Northern gannets; Breeding conditions; Hematological indicators of stress